Examining the status of spiritual health among students at the autonomous campus of Kermanshah University of Medical Sciences in 2016 - Arash Ziapour; Neda Kianipour; Shahram Saeidi; Alireza Zangeneh (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: Spiritual well-being is regarded both as one of the major dimensions of health among human beings and a prominent approach to improving public health. So, given the significance of this aspect of health, the present study aimed to Examining the status of spiritual health among students at the autonomous campus of Kermanshah University of Medical Sciences in 2016. Method: In this descriptive and analytical study, the statistical population comprised 346 students at the autonomous campus, Dentistry and Pharmaceuticals, Kermanshah University of Medical Sciences in 2016, and all of them were selected by census method in the study. For data collection, the 20-item spiritual well-being scale by Paloutzian & Ellison (1982) was utilized. To analyze data, the t-test and ANOVA were employed. All ethical issues were observed. Moreover, the authors did not report conflict of interest. Results: The results of the present study revealed that the spiritual well-being of students was average (71.86±4.84), and of all demographic variables under study, only the variable of gender was correlated with the mean score of spiritual well-being. Furthermore, the students' scores of religious well-being measured higher than that of their existential well-being. Conclusion: According to the dominant religious culture in Iranian society, expected influences of religious as a compatibility source is normal. Therefore, it is necessary for the protection of young people pay attention to their spiritual dimension, to witness the impact of such care and create a sense of peace and healing in patients. For downloading the full-text of this article please click here.